Development of an automated optimization system of the transshipment complex - Забара, Станіслав Сергійович; Дехтярук, Микола Трохимович (Eastern-European Journal of Enterprise Technologies, 2015)
Based on optimality criteria, an automated optimization system of the port industrial-transshipment complex was developed. The automated system is implemented as a software computer complex, which is developed using visual design environment EmbarcaderoC++Builder XE5. Software complex consists of a main form Form1, with the component TabControl, consisting of a set of bookmarks bars. Each bookmark represents a separate subroutine, which allows to perform optimal cargo distribution among the berths according to two options of cargo operations (direct and through the warehouse) using existing groups of berths (bulk, general, grain) and available cargo handling mechanisms and human resources by the optimality criteria - maximum cargo turnover, minimum cargo handling time and minimum cargo handling cost. As a result of the optimal redistribution of the cargo and resources of the port industrial-transshipment complex, according to groups of berths and options of loading operations, the calculation of cost savings when performing reloading operations was carried out.